Faktor-Faktor yang Berhubungan dengan Status Gizi pada Balita di Puskesmas Kecamatan Gunung Megang Kabupaten Muara Enim - Ayu Puspita Sari; Siti Fatimah; Surti Anggraeni; Rika Hairunisyah; Rita Kamalia (Malahayati Nursing Journal, 2025)
ABSTRACT Insufficient nutritional intake given to children can have a major impact on the child's nutritional status. Underlying factors such as maternal education, economic status, history of infection. There has never been any similar research in Gunung Megang District. This study aim to determine the factors related to the nutritional status of toddlers at the Gunung Megang District Health Center, Muara Enim Regency in 2024. This research is a quantitative study with a cross-sectional approach. This research was carried out in April - May 2024. The population in this study were all toddlers aged 1-5 years at the Gunung Megang District Health Center, Muara Enim Regency in 2024, totaling 213 people with a sample size of 60 people. Data analysis uses frequency distribution and chi square. There is a relationship between maternal education and the nutritional status of toddlers at the Gunung Megang District Health Center, Muara Enim Regency in 2024 (p value 0.000; CC 0.500). There is a relationship between economic status and nutritional status in toddlers at the Gunung Megang District Health Center, Muara Enim Regency in 2024 (P value 0.000; CC 0.511). There is a relationship between infectious diseases and nutritional status in toddlers at the Gunung Megang District Health Center, Muara Enim Regency in 2024 (p value 0.000; CC 0.481).  Education, economic status, infectious diseases are factors in the nutritional status of toddlers. Health education is needed to increase mothers' knowledge of nutritious food at low prices and prevent infections among toddlers. Keywords: Education, Economic Status, Infection, Nutritional Status  ABSTRAK Asupan nutrisi yang tidak cukup diberikan pada anak dapat berdampak besar pada status gizi anak. Faktor yang mendasari seperti Pendidikan ibu, status ekonomi, riwayat infeksi. Belum pernah ada penelitian sejenis di Kecamatan Gunung Megang. Tujuan untuk mengetahui  Faktor-Faktor Yang Berhubungan Dengan Status Gizi     Pada Balita Di Puskesmas Kecamatan Gunung Megang Kabupaten Muara Enim Tahun 2024. Penelitian ini merupakan penelitian kuantitatif dengan pendekatan crossectional. Penelitian ini telah dilaksanakan pada bulan April - Mei  2024. Populasi dalam penelitian ini adalah semua balita usia 1-5 tahun di Puskesmas Kecamatan Gunung Megang Kabupaten Muara Enim Tahun 2024 sebanyak 213 orang dengan jumlah sampel 60 orang. Analisis data menggunakan distribusi frekuensi dan chi square. Ada hubungan pendidikan ibu dengan status gizi pada balita di puskesmas Kecamatan Gunung Megang Kabupaten Muara Enim tahun 2024 (p value 0,001; CC 0,443). Ada hubungan status ekonomi dengan status gizi pada balita di puskesmas Kecamatan Gunung Megang Kabupaten Muara Enim tahun 2024 (P value 0,000; CC 0,488). Ada hubungan penyakit infeksi dengan status gizi pada balita di puskesmas Kecamatan Gunung Megang Kabupaten Muara Enim tahun 2024 (p value 0,000; CC 0,469). Pendidikan, status ekonomi, penyakit infeksi merupakan faktor dalam status gizi balita. Pendidikan kesehatan diperlukan untuk meningkatkan pengetahuan ibu dalam makanan bergizi dengan harga murah dan mencegah infeksi. Kata Kunci: Pendidikan, Status Ekonomi, Infeksi, Status Gizi